Gay conservatives : group consciousness and assimilation - Cimino, Kenneth W. (Haworth, 2007)
"Recent studies show that the vast majority of the LGBT community considers itself politically liberal. Yet nearly 25% of all LGBT voters helped re-elect George W. Bush in 2004. Who are these people and why did they make that choice? Gay Conservatives examines why conservative LGBTs join political groups and support political candidates that not only don't favor policies that benefit the LGBT community, but in some cases, advocate prejudicial policies. This book looks at the impact of "group consciousness" on conservative LGBTs and how it affects political power and social construction."--BOOK JACKET.